Persepsi Guru terhadap Pengembangan Literasi di SD Negeri 124 Palembang Pada Implementasi Kurikulum Merdeka - Lestari, Dinna; Agustina, Weni (Yayasan Sembilan Pemuda Indonesia, 2024)
This study aims to explore teachers’ perceptions of literacy develpoment at state elementary School 124 Palembang in the implementation of the Merdeka Curriculum. Using a qualitative approach through the case study method, data were obtained through in depth interviews and observations of ten teachers who were directly involved in teaching literacy. The result of this study show that the majority of teachers have a positive perception of the flexibility offered by Merdeka curriculum in developing literacy. Limited despite being faced with a number of challenges such as lack of resources and limited training. This study provides important insight regarding the factors that influences the successful implementation of the independent curriculum in developing literacy in elemtary school. The novelty of this research lies in understanding how teachers perceptions of literacy developmentcan be integrated into the independent curriculum at the elemetary school level. The contribution of this study is to provided insight for policy makers and school regarding the important of greater support, both in term of resources and training, to strengthen literacy implementation in this flexible curriculum.